Legal aspects of athletes' image rights usage in the light of marketing activities - Krzysztof M. Westfal (Nicolaus Copernicus University in Toruń, 2016)
Usually the law is at least one step behind the market demands. Economic potential of athletes' image rights has been recognized by marketing specialists many years ago. Selling image rights brings huge amounts of money to professional athletes each year. In market practice and in the realities of professional sport, commercial character of the image rights has become a fact.                 Also noticeable tendencies in development of Polish law interpretation seems to acknowledge that fact. Latest attempts of redefining nature of the image rights as economical or mixed economical-personal one deserves for approval.                 The importance of the issue of professional athletes' image has found its reflection in legislation. Art. 14 par. 1-3 of the Sports Act of 25th June 2010 sets lex specialis to art. 23 and 24 paragraphs 1-3 of the Polish Civil Code as well as to art. 81 par. 1 and 2 of the Copyright and Related Rights Act of 4th February 1994 which sets general legal frameworks for image rights in Poland. Abovementioned provisions of the Sport Act grants the Polish sports unions and the Polish Olympic Committee with the exclusive right to use, in order to their business goals, image of the athletes wearing, respectively, the Polish national team outfit or the Olympic team outfit.                 Specific legal provisions functioning in relation to the professional athletes' image were also the subject of the case law of the Supreme Court. Of key importance for the interpretation of art. 14 paragraphs 1-3 of the Sports Act has a Supreme Court judgment of 16th December 2009, I CSK 160/09, which was issued on the basis of art. 33 paragraph 1 and 2 of the repealed Qualified Sport Act.                 For issues of athletes image usage not without significance is the fact that professional athletes usually have the status of a commonly known persons. In the light of art. 81 par. 2 of Sports Act disseminating the image of an athlete who is commonly known person as well, does not require the consent of such a person, provided that the image has been made in connection with the performance of public functions, in particular social or professional ones.                 Regarding to the issue of entities authorized to disseminating athletes image there is considerable diversity. Depending on the factual situation, except of an athlete itself, such entitled entity might become the Polish Olympic Committee, the Polish sport union, sport club or organization for collective management of rights of athletes.                 Having regard to the multidimensional issue of the athletes' image, and bearing in mind how common practice concluding of the marketing contracts concerning image rights has become, it should be postulated that observable changes concerning issue in question, shall be made towards meeting the needs espoused by the market.